Challenging T > MIC Using Meropenem vs. Escherichia coli and Pseudomonas aeruginosa - Nussbaumer-Pröll, A.; Eberl, S.; Kurdina, E.; Schmidt, L.; Zeitlinger, M. (Frontiers in Pharmacology, 2022)
For meropenem 40%T>MIC is associated with optimal killing of P. aeruginosa and E. coli. However, it is unknown how the distribution of %T>MIC through a treatment day impacts the antimicrobial effect. Therefore, we investigated the antibiotic activity of meropenem, precisely if 40%T>MIC is achieved in one single long period (single dose), 2x20% periods (dosing-bid) or 3x13.3% (dosing t.i.d.) thereby keeping the overall period of T>MIC constant. TKC with P. aeruginosa-ATCC-27853 and E. coli-ATCC-25922 and 5 clinical isolates each, were implemented over 24hours in MHB with concentrations from 0.25xMIC-32xMIC. Periods over and under MIC were simulated by centrifugation steps (discarding supernatant and refilling with fresh MHB). Double and triple dosing involved further addition and removal of antibiotic. Complementary growth controls (GC) with and without centrifugation steps were done and the emergence of phenotypical resistance was evaluated (repeated MIC-testing after antibiotic administration). No impact of centrifugation on bacterial growth was seen. TKC with P. aeruginosa showed best killing in the triple dosage, followed by the double and single dose. In multiple regimens at least a concentration of 4xMIC was needed to achieve a recommended 2-3 log10 killing. Likewise, a reduction of E. coli was best within the three short periods. Contrary to the TKCs with P. aeruginosa we could observe that after the inoculum reached a certain CFU/mL (≥10^8), no further addition of antibiotic could achieve bacterial killing (identified as inoculum effect). For P. aeruginosa isolates resistance appeared within all regimens, the most pronounced was found in the 40%T>MIC experiments indicating that a single long period might accelerate the emergence of resistance. Contrary, for E. coli no emergence of resistance was found. We could show that not solely the %T>MIC is decisive for an efficient bacterial eradication in vitro, but also the distribution of the selected %T>MIC. Thus, dividing the 40%T>MIC in three short periods requested lower antibiotic concentrations to achieve efficient bacterial killing and reduced the emergence of resistance in P. aeruginosa isolates. The distribution of the %T>MIC did impact the bacterial eradication of susceptible pathogens and might play an even bigger role in infections with intermediate or resistant pathogens.